Georgia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in the Republic of Georgia during 1995. The paper highlights that in 1995, the economy of Georgia continues to face severe bottlenecks, especially arising from energy shortages. However, there are signs of increased confidence and a recovery in the first half of 1995, fostered by political stability and the initial fruits of financial stabilization and structural reform. In 1995, agricultural output and cargo transport appear to have increased, and retail trade is growing quickly. Industrial and construction activity, however, remains limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet